2011
DOI: 10.1371/journal.pone.0021354
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Waggle Dance Motion of Honeybees for the Design of a Biomimetic Honeybee Robot

Abstract: The honeybee dance “language” is one of the most popular examples of information transfer in the animal world. Today, more than 60 years after its discovery it still remains unknown how follower bees decode the information contained in the dance. In order to build a robotic honeybee that allows a deeper investigation of the communication process we have recorded hundreds of videos of waggle dances. In this paper we analyze the statistics of visually captured high-precision dance trajectories of European honeyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 19 publications
2
55
0
1
Order By: Relevance
“…Eiri and Nieh [23] found that a single imidacloprid dose of 0.21 ng/bee (24 ppb) resulted in bees that continued to visit a rich 2.0 M (55% w/w) sucrose solution 24 hours later. These bees did not exhibit any impairments in flight, walking, or waggle dancing, a task requiring complex coordination [61]. Treated bees simply performed fewer dance circuits than controls, suggesting that they perceived the food, which was pure and free of any imidacloprid, as being less valuable for the colony [23].…”
Section: Discussionmentioning
confidence: 94%
“…Eiri and Nieh [23] found that a single imidacloprid dose of 0.21 ng/bee (24 ppb) resulted in bees that continued to visit a rich 2.0 M (55% w/w) sucrose solution 24 hours later. These bees did not exhibit any impairments in flight, walking, or waggle dancing, a task requiring complex coordination [61]. Treated bees simply performed fewer dance circuits than controls, suggesting that they perceived the food, which was pure and free of any imidacloprid, as being less valuable for the colony [23].…”
Section: Discussionmentioning
confidence: 94%
“…They then created a RoboBee that performed those movements for an audience of bees inside the hive. In its early iteration, the robot could entice bees to leave the hive, but couldn't convey to them the direction of the food source 2 . Since then, the researchers have improved both the software and the hardware in the robot, and now some bees do follow its signal to the food source.…”
Section: Follow the Cuesmentioning
confidence: 99%
“…Robots have been used extensively to investigate social interactions, with a focus on group behavior and social dynamics. They appear to be extremely effective for this sort of task and have been used to manipulate group behavior in terms of shelter choice (cockroaches Periplaneta americana , Asadpour et al, ; Halloy et al, ), inter‐individual distances, shoal orientation (sticklebacks Gasterosteus aculeatus , Faria et al, ), and foraging behavior (house finches Haemorhous mexicanus , Fernández‐Juricic et al, ; and bees Apis mellifera carnica , Landgraf, Rojas, Nguyen, Kriegel, & Stettin, ; Landgraf, Oertel, Kirbach, Menzel, & Rojas, ). Observation of interactions with conspecifics or humans also modulates an animal's responses toward a robot (dogs Canis lupus familiaris , Lakatos et al, ).…”
Section: Social Interactionsmentioning
confidence: 99%
“…Faria et al, 2010), and foraging behavior (house finches Haemorhous mexicanus, Fernández-Juricic et al, 2006; and bees Apis mellifera carnica,Landgraf, Rojas, Nguyen, Kriegel, & Stettin, 2011;Landgraf, Oertel, Kirbach, Menzel, & Rojas, 2012). Observation of interactions with conspecifics or humans also modulates an animal's responses toward a robot (dogs Canis lupus familiaris,Lakatos et al, 2014).…”
mentioning
confidence: 99%